Fatigue in COPD and the impact of heart disease comorbidity : a population-based study - Stridsman, Caroline; Mullerova, Hana; Skär, Lisa; Lindberg, Anne (Luleå tekniska universitet, Institutionen för hälsovetenskap, 2011)
Background: Fatigue is a common symptom among people with COPD. However, there are few studies describing fatigue in COPD and the impact of comorbidity, none of them population based.Aim: To describe fatigue in COPD by disease severity according to GOLD, and the impact of self-reported heart disease.Methods: The Functional Assessment of Chronic Illness Therapy (FACIT)- Fatigue scale was used to assess fatigue; lower scores represent worse fatigue (0-52). Data were collected in 2007 from the Obstructive Lung Disease in Northern Sweden (OLIN) COPD cohort; 564 subjects with COPD, with a distribution of disease severity representative for the general population, and 786 non-COPD subjects.Results: Median FACIT-F score was 44.0 in COPD subjects, significantly lower compared to 46.0 in non-COPD (p=0.006). Score decreased by disease severity: 46.0, 43.7, and 37.5 in GOLD stage I, II, and III-IV (I vs II p=0.020, II vs III-IV p=0.035). There was no significant difference between stage I and non-COPD. In subjects without heart disease, there were lower scores in stage II, 45.0 and III-IV, 38.5 compared to non-COPD, 47.0 (p=0.005 and p=0.205). In subjects with heart disease, only stage III-IV had significantly lower scores than non-COPD, 30.5 vs 42.0 (p=0.030). Subjects with heart disease reported lower scores than those without heart disease at all severities of COPD (non-COPD: 42.0 vs 47.0, p<0.001, stage I: 40.5 vs 48.0, p<0.001, stage II: 40.0 vs 45.0, p=0.008 and stage III-IV: 30.5 vs 38.5, p=0.051).Conclusion: Fatigue increases with GOLD-defined disease severity, but the score is not significantly different from non-COPD until stage II. Heart disease increases fatigue in both COPD and non-COPD. Godkänd; 2011; 20120815 (andbra)